2020
DOI: 10.3390/polym12010101
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/Carbon Nanotube Hybrid Nanocomposites: Effect of Compression Molding and Fused Filament Fabrication on Properties

Abstract: The present work reports on the production and characterization of acrylonitrile butadiene styrene (ABS) hybrid nanocomposite filaments incorporating graphene nanoplatelets (GNPs) and carbon nanotubes (CNTs) suitable for fused filament fabrication (FFF). At first, nanocomposites with a total nanofiller content of GNP and/or CNT of 6 wt.% and a GNP/CNT relative percentage ratio of 0, 10, 30, 50, 70, and 100 were produced by melt compounding and compression molding. Their mechanical, electrical resistivity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 63 publications
(74 reference statements)
2
49
1
Order By: Relevance
“…37,53 The presence of both fillers should lead to larger contact area and better interaction between CNTs and the matrix. 54 In our case, hybrid samples show a homogenous degree of filler dispersion even if some bundles of MWCNTs have been observed (Figure 8(c)).…”
Section: Preliminary Characterizationssupporting
confidence: 48%
“…37,53 The presence of both fillers should lead to larger contact area and better interaction between CNTs and the matrix. 54 In our case, hybrid samples show a homogenous degree of filler dispersion even if some bundles of MWCNTs have been observed (Figure 8(c)).…”
Section: Preliminary Characterizationssupporting
confidence: 48%
“…However, further studies should be carried out in future on resin-curing to have a better understanding on how sepiolite chemically affects UF-resin. Chemical studies like resin-curing and FTIR would possibly explain why the increases in hardness values were so low, contrary to some previous studies demonstrating the high impact of low amounts of nanofillers on different properties of resins and adhesives [46][47][48][49]. Regression analysis among different properties showed the high and significant R-square values between all of them.…”
Section: Resultscontrasting
confidence: 59%
“…In particular, it was shown that the addition of MWCNT improved highly the electrical conductivity, but significantly increased the viscosity of materials that consequently required high-temperature FFF process (280 • C). We also observed that proper mixing of 3 wt% MWCNT and 3 wt% GNP provide a possible compromise between relatively easy processability and an acceptable enhancement of performances (i.e., mechanical and specific electrical properties), resulting in the production of ABS nanocomposite filaments for 3D printing with resistivity of 4.1 Ω.cm [34]. We also found that the electrical percolation threshold of nanocomposites was achieved at 0.9 wt% for MWCNT [16].…”
Section: Introductionmentioning
confidence: 61%